EVALUATION OF WATER QUALITY FOR THE NILE FISH-FLOATING NET CAGE AQUACULTURE SYSTEM AT BANGKA BELITUNG UNIVERSITY - andri kurniawan; Denny Syaputra; irvani Irvani (Journal of Aquatropica Asia, 2023)
The water quality feasibility is an important factor in aquaculture activities and increasing the productivity of cultivated fish. The Bangka Belitung University (UBB) is developing nile fish cultivation in earthen ponds using a floating net cage system. However, there has been no study related to the quality of water in earthen ponds that can be used to determine the feasibility of using these ponds for fish farming, especially nile fish. This study aimed to evaluate the water quality for the nile fish-floating net cage aquaculture system at Bangka Belitung University. The physical and chemical parameters observed were pH, temperature, DO, BOD, COD, NH3-N, PO4-P, NO3-N, NO2-N, NH3, C-organic, and minerals. Measurements of fish performance were observed in the form of SR, ADG, SGR, absolute growth (length and weight), and FCR. The results showed that in general the water quality of the earthen pond of UBB was still feasible for nile fish cultivation which produced SR (100%), ADG (0.20 g/day), SGR (2.18%/day), and FCR (1, 3). Water quality engineering can be done by adding a water wheel to increase the concentration of dissolved oxygen and also reduce the activity of Fe and other minerals that cause acidity and inhibit the growth rate of nile fish